Analysis of the Coefficient of Performance in a Cascade Flash Chamber Cooling System for Fishing Vessels - Shelfira Priti Chantika; Dr. Fajri Ashfi Rayhan (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2026)
Global climate change is closely related to increasing greenhouse gas emissions, including those generated by energy-intensive refrigeration systems on fishing vessels. Conventional onboard cooling systems often operate at relatively low efficiency, resulting in high fuel consumption and environmental impact. This study aims to analyze the coefficient of performance (COP) of a cascade refrigeration system with a flash chamber for fishing vessel applications by evaluating the influence of refrigerant selection and intermediate operating temperature. A steady-state thermodynamic simulation model was developed using Engineering Equation Solver (EES). Three refrigerants, namely R134a, R404A, and R407C, were investigated under intermediate temperature variations of 10–30 °C. The model was validated through comparison with reference data from the literature. Simulation results include compressor power consumption, condenser heat rejection, evaporator heat absorption, and COP values. The results indicate that intermediate temperature significantly affects compressor work distribution between the low-stage and high-stage compressors. Among the evaluated refrigerants, R134a achieved the highest COP under all operating conditions, while R404A showed lower condenser heat rejection and cooling capacity. Overall, the cascade refrigeration system with a flash chamber demonstrates improved energy performance and offers a promising solution to reduce fuel consumption and greenhouse gas emissions in marine refrigeration applications.